Scientific Analysis And Results Of The Stone Crucible - Kholyigitov Omonboy Alimovich (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The article presents scientific analyzes on the stone crucible. A new design of the scoop is proposed, and the effect of the built-in deflector device on the efficiency of catching small stones in cotton is experimentally studied. When the cotton material enters the stone holding chamber, it is hit by a returner (otrajatel) installed in the chamber to separate small stones and other impurities such as sand among the cotton. The front part of the returner is equipped with self-rotating rollers, and the distance between the rollers is 10 mm smaller than the size of the cotton pellets